Journal of bridge engineering
The Journal of Bridge Engineering publishes papers about all aspects of the art and science of bridge engineering. The journal publishes research that advances the practice and profession of bridge engineering and papers about issues, projects, materials, design, fabrication, construction, inspection, evaluation, safety, performance, management, retrofitting, rehabilitation, repair, and demolition.